Bureaucratic Law Transformation and Trade Union Fragmentation in Thailand and Japan in the Context of Free Trade - Ramaraj, Somchai; Winichagoon, Rameshprabu; Pinlaor, Pattanee; Almetra, Rhamos; Enomoto, Katsuhiko (International Journal of Law and Public Policy (IJLAPP), 2024)
To achieve economic development, a country must cooperate with other nations. This often involves a partnership where one country provides workers, while foreign investors contribute significant capital. To sustain such trade relationships, bureaucratic reform is sometimes necessary. These reforms aim to enhance administrative efficiency and economic competitiveness but can also lead to the fragmentation of trade unions, which impacts workers' protection and rights. This research explores the transformation of bureaucratic law and trade union fragmentation in Thailand and Japan within the context of free trade. A qualitative comparative study method was employed to analyze the effects of these reforms in both countries. In Thailand, reforms aimed at simplifying the licensing process and reducing regulations have been successful in attracting foreign investment and accelerating economic growth. However, they have also increased job uncertainty and weakened social protection. In Japan, while traditional labor unions persist, the increasing fragmentation has resulted in uneven worker protection. This analysis reveals that the social and economic effects of these changes are complex and require careful policy consideration to balance economic growth with worker protection. The study recommends comprehensive labor law reforms, increased social dialogue, and stronger support for new trade unions to ensure fair and sustainable worker protections in both countries.